Aḥmad Muḥammad Nu‘mân et la construction d’une identité nationale yéménite - François Burgat (Revue des Mondes Musulmans et de la Méditerranée)
The testimony of Ahmed Num’an, co-founder of the Free Yemeni Movement addresses two different issues. First, it highlights the causes of the political backwardness of the Yemen of the first half of the XXth century: poverty and illiteracy are upheld by an archaic educational system on the one hand as well as by the religious traditionalism and the exploitation of sectarian divisions (sunni/chia) to which the Imam resorts to ensure its authority. Nu’man also makes it possible to understand the paradoxical character of the role played by the Egyptians in the process of modernisation. By strongly supporting the 1962 republican revolution, Nasser did give to the young Yemeni Republic the means of his military victory “by the top”. But by evicting Nu’man and the founders of the main modernisation movement, in favour of his own agents, he has distressed the endogenous character of the dynamics of modernisation, depriving it probably, of part of its own resources. By reversing only, instead of ending the mechanism of sectarian stigmatization (sunni vs shia), the Egyptian influence undoubtedly interfered until nowadays, with the process of building a national identity.